Spatial Variability in Environmental Science Patterns, Processes, and Analyses - Tiefenbacher, John P.; Poreh, Davod (IntechOpen, 2020)
Spatial Variability in Environmental Science - Patterns, Processes, and Analyses includes eight studies that examine the issue of spatial variability in four areas of the environmental sciences - atmospheric science, geological science, biological science, and landscape science. The topics range from monitoring of wind, the urban heat island, and atmospheric pollution, to coastal geomorphology, landscape planning and forest ecology, the problem of introduced species to regional ecologies, and a technique to improve the identification of human constructions in semi-natural landscapes. A small volume can only offer a small glimpse at the activities of scientists and insights into environmental science, but the array of papers herein offers a unique view of the current scholarship.